Caring for Patients with Substance Use Disorders: Addressing a Missed Opportunity in the Hospital - Simon, Rachel Elizabeth (The Hastings Center report, 2018)
As physicians, we have seen patients with substance use disorders leave the hospital against medical advice, slipping through the cracks of our health care system. In fact, despite a high burden of life-threatening illnesses, patients with SUDs are at a nearly threefold increased risk of leaving the hospital against medical advice. Leaving against medical advice is associated with an increased thirty-day mortality rate as well as an increased rate of hospital readmission. When a patient leaves in this way, the health care system loses the opportunity to engage with someone who is struggling with an SUD and whose health is at imminent risk. Fortunately, there are ways to address some of these challenges within existing organizational frameworks. Addiction consult teams and supervised injection facilities are two interventions that have proven successful.